RESPON TANAMAN KUBIS (Brassica olacea var. capitata) TERHADAP KOMBINASI APLIKASI PUPUK ORGANIK DAN ANORGANIK - Rini, Erin Puspita; Sugiyanta, Sugiyanta (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[CABBAGE (Brassica olacea var. capitata) GROWTH AND YIELD AFFECTED BY COMBINATION OF ORGANIC AND INORGANIC FERTILIZER APPLICATIONS]. The use of organic fertilizer increasingly sought by farmers due to the increase in demand for organic products by consumers and also awareness of the sustainability of the land. The use of organic fertilizers in the cultivation alone could improve the soil quality but needs to be balanced with inorganic fertilizers to meet the nutrient adequacy. This study aims to examine the effect of organic and inorganic fertilizers combination on the growth and cabbage yield, and also to determine the most efficient dosage combination of organic and inorganic fertilizers. This research was conducted at the IPB Pasir Sarongge Experimental Station, Cianjur, West Java from November 2020 to February 2021. The study was compiled using RCBD with 4 replications and 7 treatments. The results showed the combination of 0.75 doses of inorganic fertilizer (150 kg/ha of urea, 75 kg/ha SP36, and 75 kg/ha KCl) and 3 tons/ha of organic fertilizer could increase 14.87 to 15.44% plant height and the number of leaves at 12.82 -15.11% compared to the same dose of inorganic fertilizer treatment alone. The combination of 1 dose (200 kg/ha of urea, 100 kg/ha SP36, and 100 kg/ha KCl) inorganic fertilizer application and 2 tonnes/ha of organic fertilizer could increase 50,60% yield/plot and yield/ha cabbage than 1 dose of inorganic fertilizer treatment..